Insights into Lipid-Based Delivery Nanosystems of Protein-Tyrosine Kinase Inhibitors for Cancer Therapy - Josef Jampilek; Katarina Kralova (MDPI AG, 2022)
According to the WHO, cancer caused almost 10 million deaths worldwide in 2020, i.e., almost one in six deaths. Among the most common are breast, lung, colon and rectal and prostate cancers. Although the diagnosis is more perfect and spectrum of available drugs is large, there is a clear trend of an increase in cancer that ends fatally. A major advance in treatment was the introduction of gentler antineoplastics for targeted therapy-tyrosine kinase inhibitors (TKIs). Although they have undoubtedly revolutionized oncology and hematology, they have significant side effects and limited efficacy. In addition to the design of new TKIs with improved pharmacokinetic and safety profiles, and being more resistant to the development of drug resistance, high expectations are placed on the reformulation of TKIs into various drug delivery lipid-based nanosystems. This review provides an insight into the history of chemotherapy, a brief overview of the development of TKIs for the treatment of cancer and their mechanism of action and summarizes the results of the applications of self-nanoemulsifying drug delivery systems, nanoemulsions, liposomes, solid lipid nanoparticles, lipid-polymer hybrid nanoparticles and nanostructured lipid carriers used as drug delivery systems of TKIs obtained in vitro and in vivo.